A new species of Rhopalorhynchus (Pycnogonida: Colossendeidae) from Lizard Island, North Queensland, Australia - Staples, David A. (Zootaxa, 2009)
A new species of pycnogonid of the genus Rhopalorhynchus Wood-Mason, 1873 is described from the shallow waters of Lizard Island, north Queensland, increasing the number of Rhopalorhynchus species from Queensland to three. One female and two males were collected from coral rubble sortings gathered by hand dredge. The new species is compared with its congeners and the status of R. gracillimus Carpenter, 1907 is reviewed. Variability in R. tenuissimus (Haswell, 1884) is recorded.